Peran Pendidikan Teknologi Dalam Menyiapkan Sumber Daya Manusia Yang Kompeten Di Sektor Industri - Razan, Hilmy; Rizki , Moch; Wahjono, Imam Sentot (CV ODIS, 2025)
Technology education has an important role in preparing competent human resources (HR) in the industrial sector. In the era of globalization and rapid technological development, technical skills and relevant knowledge are the keys to success in the industrial world. Technology education focuses on developing the practical skills needed by the workforce to face the challenges of modern industry. Through a curriculum tailored to industry needs, this education helps increase the competitiveness and productivity of human resources. Apart from that, educational technology also contributes to the development of innovation and efficiency in the production process. Therefore, integration between educational technology and the industrial sector is very important to create human resources who are not only skilled, but also ready to face ever-changing technological developments.